Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2021
DOI: 10.3389/fnins.2021.665017
|View full text |Cite
|
Sign up to set email alerts
|

Modern Technology in Multi-Shell Diffusion MRI Reveals Diffuse White Matter Changes in Young Adults With Relapsing-Remitting Multiple Sclerosis

Abstract: ObjectiveTo characterize microstructural white matter changes related to relapsing-remitting multiple sclerosis using advanced diffusion MRI modeling and tractography. The association between imaging data and patient’s cognitive performance, fatigue severity and depressive symptoms is also explored.MethodsIn this cross-sectional study, 24 relapsing-remitting multiple sclerosis patients and 11 healthy controls were compared using high angular resolution diffusion imaging (HARDI). The imaging method includes a m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(16 citation statements)
references
References 84 publications
(97 reference statements)
0
16
0
Order By: Relevance
“…Regarding the bundles, our results suggest that all bundles that show high consistency, whether extracted on whole or along the bundles, are involved in different pathologies, aging or development. This is particularly the case for AF, ILF, IFOF, CST, UF and CG which have very good consistency per se (Dice score) (Atkinson-Clement et al, 2017; Beaudoin et al, 2021; Bergamino et al, 2020; Coelho et al, 2021). A more moderate observation can be made regarding some parts of the corpus callosum, which showed more variable consistency of data.…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…Regarding the bundles, our results suggest that all bundles that show high consistency, whether extracted on whole or along the bundles, are involved in different pathologies, aging or development. This is particularly the case for AF, ILF, IFOF, CST, UF and CG which have very good consistency per se (Dice score) (Atkinson-Clement et al, 2017; Beaudoin et al, 2021; Bergamino et al, 2020; Coelho et al, 2021). A more moderate observation can be made regarding some parts of the corpus callosum, which showed more variable consistency of data.…”
Section: Discussionmentioning
confidence: 90%
“…Other techniques like magnetization transfer imaging (MTI, M. Kim & Cercignani, 2014; Wolff & Balaban, 1989) are also increasingly used to examine changes in the myelin content of WM. Key measures of WM microstructure derived from these models are sensitive to changes in a healthy population (Alexander, 2017; Beck et al, 2021; Boukadi et al, 2019; Honnedevasthana Arun et al, 2021; Koshiyama et al, 2020; Munsch et al, 2021; Uddin et al, 2019) or in pathological conditions (Beaudoin et al, 2021; Brown et al, 2017; Granziera et al, 2021; Laule & Moore, 2018; Lu et al, 2021; Rahmanzadeh et al, s. d.; Schneider et al, 2017). In addition, studies have also shown the effect of a treatment or therapeutic intervention on WM measures in clinical trials (Arnold et al, 2022; Gurevich et al, 2018; Roy et al, 2021; Vavasour et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Fifteen studies were identified that evaluated the relationship between fatigue and dMRI measures, all of which used DTI and one used HARDI [139]. Seven out of fifteen studies did not report any significant findings (Table 1) [66, 105, 108, 110, 138, 139, 150] and 8/15 found significant associations (Tables 1 and 3).…”
Section: Resultsmentioning
confidence: 99%
“…Five studies were identified that assessed associations between structural connectivity measures and depression in pwRRMS, four of which used DTI [29, 98, 136, 138] and one used HARDI [139] (Tables 1 and 3), but only three found statistically significant relationships between structural connectivity and depression in pwRRMS [29, 136, 139].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation